Penurunan Aktivitas Biofilm Strain MRSA 22156 oleh Tanaman Saga (Abrus precatorius L.) - Bq. Mutmainnah; Ni’matuzahroh Ni’matuzahroh (Department of Biology Education, FSTT, Mandalika University of Education, Indonesia., 2023)
The aim of this research is to determine the effect of using saga extract on bacterial biofilm growth, and to determine the most appropriate dose of saga extract in reducing MRSA 22156 biofilm activity. This research uses the Dowd method to determine the total flavonoid content of A. precatorius L leaves. Treatment reduction in MRSA 22156 biofilm growth using the Plate Biofilm Assay method with three repetitions. The results of the research show that total flavonoids can reduce the growth of MRSA 22156 biofilms. The use of total flavonoids from A. precatorius L. leaves in concentrations of 800 mgL-1 to 25 mgL-1 has been proven to have an effect on biofilm growth activity as indicated by the reduction in MRSA 22156 biofilm growth by 67.9% and 25%. The ethanol extract of A. precatorius L. has anti-biofilm activity in reducing the growth of Staphylococcus aureus bacteria that are resistant to Methicillin.